Optimal dynamic response of composite structures using a hierarchical genetic algorithm - Carlos Alberto Conceição António (2004)
An optimisation model for structural reliability maximization of compositestructures under dynamic loading conditions is proposed. The failure probability isobtained using a procedure based on level 2 reliability analyses adapted for dynamicresponse. The material properties of the ply are the random normal variables. Theoptimisation process is based on a Hierarchical Genetic Algorithm where a masterpopulation evolves with a net of slave sub-populations. The proposed topology aimsto link the Most Probable failure Point search with the maximisation of structuralreliability. The design variables are the ply angles of the composite laminates.